Crigler-Najjar Syndrome Type 2 in a Young Adult - Haque, Md. Azizul; Sharmin, Laila Shamima; Harun or Rashid, Mohd; Alim, MA; Ekram, ARM Saifuddin; Mowla, Syed Ghulam Mogni (Journal of Medicine, 2011)
Crigler-Najjar syndrome type 2 in an autosomal recessive congenital non-hemolytic hyperbilirubinemia caused by UDP-glucuronosyltransferase deficiency. Only a few hundred cases have been described in the literature so far. We are reporting Crigler-Najjar syndrome type 2 in an 18 year old female born out of consanguineous marriage. Keyword: Crigler-Najjar syndrome; UDP-glucuronosyltransferase; Bangladesh DOI: 10.3329/jom.v12i1.6359 J Medicine 2011; 12 : 81-85